2021
DOI: 10.31128/ajgp-07-20-5550
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative understandings of access to primary care services for consumers who use methamphetamine

Abstract: Background and objectiveGeneral practice is the most common source of healthcare for people who use methamphetamine. The aim of this study was to explore primary care providers' understandings of access to and service utilisation by this group. MethodsSemi-structured interviews were conducted with general practitioners, practice nurses and alcohol and other drug service providers from two large towns in rural Victoria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…In Australia, primary health care services play an important role in the management and/or referral for the treatment of mental illness (Cross and Hickie, 2017). Consumers who use methamphetamine report primary care services as their most common point of contact with the health care system (McKetin et al, 2018; Quinn et al, 2020), yet some primary care providers report they do not see and/or are reluctant to provide care to this population (Ward et al, 2021). Diagnoses of anxiety and/or depression may provide a segue into an integrated model of care whereby common comorbidities (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In Australia, primary health care services play an important role in the management and/or referral for the treatment of mental illness (Cross and Hickie, 2017). Consumers who use methamphetamine report primary care services as their most common point of contact with the health care system (McKetin et al, 2018; Quinn et al, 2020), yet some primary care providers report they do not see and/or are reluctant to provide care to this population (Ward et al, 2021). Diagnoses of anxiety and/or depression may provide a segue into an integrated model of care whereby common comorbidities (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…emergency departments and psychiatric admissions); future research would benefit investigating the triggers for what motivates people who use methamphetamine and comorbidly experience anxiety or depression to seek either acute or non-acute health services for mental health, especially for those who smoke methamphetamine. Evidence from the perspective of primary healthcare providers suggest that certain dimensions of access to care need to be considered, as well as the social determinants of health (Ward et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…While our findings are congruent with previous studies that found increased health service use in those experiencing co-occurring depression, anxiety, and substance use (McKetin et al, 2018;Mills et al, 2012;Quinn et al, 2013), it is important to consider the multiple dimensions of service accessibility that affect people who use methamphetamine. Access to services needs to consider the availability of appropriate services for cooccurring methamphetamine use and anxiety or depression; they also need to be affordable to the consumer, approachable, and acceptable to the individual consumers' social and cultural needs (Ward et al, 2021). Addressing the helping and hindering factors associated with engagement in health service for people that use methamphetamine and experience co-occurring methamphetamine use and anxiety or depression is crucial to closing the gap for those are not seeking mental health support that may truly benefit from it.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,12 Little is known about primary care providers' experience with the emergent "twin epidemic," particularly around practice changes within the era of the COVID-19 pandemic. 11,13 To date, only one study from Australia has explored primary care providers' perspectives on addressing methamphetamine use. 11 The sample was limited to only 8 providers in a rural area of Australia with low stimulant use rates.…”
mentioning
confidence: 99%